Seasonal effect on milk productivity and cases of mastitis in Ukrainian Brown Swiss Cows - Mylostyvyi, Roman; Milostiviy, Roman; Milostivyiy, Roman; Mylostyvyi, R. V.; Mylostyvyi, Roman V.; Mylostyvy, R.; Mylostyvyi, R.; Милостивий, Роман Васильович; Izhboldina, O. O.; Izhboldina, O.; Izhboldina, Е. А.; Izhboldina, Н.; et al. (Dnipro State Agrarian and Economic University, 2021)
Seasonality affects milk production, its composition, as well as the spread of mastitis in dairy cows. The aim of the research work was to study the way the seasons affect milk productivity and the manifestation of mastitis among Ukrainian brown Swiss cows at a commercial dairy unit, with the animals kept in naturally ventilated premises. The relationship between the indicators was assessed by Spearman’s rank-order correlation coefficient. The influence of a seasonal factor and individual air parameters on cows’ milk productivity was evaluated using Factorial ANOVA in Statistica 12 software. The results of the study revealed a high correlation between the content of milk fat and milk protein and the weather conditions (temperature, relative humidity, as well as temperature-humidity index) by seasons. Moreover, the greatest negative relationship between these characteristics was observed in spring (r = 0.4‒0.8) and in autumn (r = 0.6), and not in summer during the heat, as we had predicted earlier. The influence rate of the «season» factor was significant both in terms of the daily milk yield and milk components (51–59%) and mastitis prevalence rate in cows (56%) at the dairy unit. In general, the reduction of milk yields in summer and especially in autumn, and the spread of udder pathology in cows during this period should provide for the introduction of managerial and preventive veterinary measures to mitigate the effects of hot summer among Ukrainian Brown Swiss cows at year-round housing of animals in naturally ventilated premises. Сезонність впливає на виробництво молока, склад його компонентів, а також поширення маститів у молочних корів. Метою роботи було вивчити як впливає сезон року на молочну продуктивність та прояв маститів серед українських бурих швіцьких корів на одному із комерційних молочних комплексів при їх утриманні в природно-вентильованих приміщеннях. Взаємозв’язок між ознаками оцінювали за коефіцієнтом рангової кореляції Спірмена. Вплив сезонного фактору та окремих параметрів повітряного середовища на молочну продуктивність корів оцінювали використовуючи Factorial ANOVA в програмному забезпеченні Statistica 12. За результатами дослідження виявлено високу кореляцію між вмістом молочного жиру і молочного білка та погодними умовами (температурою, відносною вологістю, а також температурно-вологісним індексом) за сезонами року. Причому, найвищий від’ємний взаємозв’язок між цими ознаками спостерігався навесні (r = 0,4‒0,8) та восени (r = 0,6), а не влітку під час спеки, як ми передбачали раніше. Відсоток впливу фактору «сезон» із відповідними погодними умовами виявився значним як на добовий удій і компоненти молока (51–59%), так і поширеність маститів в корів (56%) на молочному комплексі. В цілому зниження надоїв корів у літній і, особливо, в осінній сезон, та поширення в цей період патології молочної залози в корів повинні передбачати впровадження управлінських і превентивних ветеринарних заходів пом’якшення наслідків спекотного літа серед поголів’я українських бурих швіцьких корів за цілорічного утримання тварин в природно-вентильованих приміщеннях.
Вплив сезону на молочну продуктивність та випадки маститу в українських бурих швіцьких корів
Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813 Іжболдіна Олена Олександрівна https://orcid.org/0000-0002-8816-2228 Калиниченко Олена Олександрівна https://orcid.org/0000-0002-5391-0281 Оріщук Оксана Сергіївна https://orcid.org/0000-0002-6140-870х Піщан Ілона Станіславівна https://orcid.org/0000-0001-5030-6348 Храмкова Ольга Миколаївна http://orcid.org/0000-0002-0697-7715 Капшук Наталя Олексіївна https://orcid.org/0000-0002-2859-2795 Скляров Павло Миколайович https://orcid.org/0000-0002-4379-9583
Keywords: influence of factors; вплив факторів; seasonality; сезонність; dairy cows; молочні корови; daily milk yield; добовий удій; fat and protein content; вміст жиру та білка